Specification for harmonized system of quality assessment for electronic components. Blank detail specification. Fixed capacitors for use in electronic equipment. Aluminium electrolytic capacitors with non-solid electrolyte. Assessment level E. (15th February 1993) - British Standards Institution,
No abstract available